Trichome Independent Resistance against Western Flower Thrips in Tomato. (1st February 2019) - Bac-Molenaar, Johanna A; Mol, Selena; Verlaan, Maarten G; van Elven, Joke; Kim, Hye Kyong; Klinkhamer, Peter G L; Leiss, Kirsten A; Vrieling, Klaas
Abstract: Western flower thrips (WFT) are a major pest on many crops, including tomato. Thrips cause yield losses, not only through feeding damage, but also by the transmission of viruses of which the Tomato Spotted Wilt Virus is the most important one. In cultivated tomato, genetic diversity is extremely low, and all commercial lines are susceptible to WFT. Several wild relatives are WFT resistant and these resistances are based on glandular trichome-derived traits. Introgression of these traits in cultivated lines did not lead to WFT resistant commercial varieties so far. In this study, we investigated WFT resistance in cultivated tomato using a F2 population derived from a cross between a WFT susceptible and a WFT resistant cultivated tomato line. We discovered that this WFT resistance is independent of glandular trichome density or trichome-derived volatile profiles and is associated with three QTLs on chromosomes 4, 5 and 10. Foliar metabolic profiles of F3 families with low and high WFT feeding damage were clearly different. We identified α-tomatine and a phenolic compound as potential defensive compounds. Their causality and interaction need further investigation. Because this study is based on cultivated tomato lines, our findings can directly be used in nowadays breeding programs.